Differential impact of ventromedial prefrontal cortex damage on "hot" and "cold" decisions under risk. - Spaniol, Julia; Di Muro, Francesco; Ciaramelli, Elisa (Cognitive, Affective & Behavioral Neuroscience, 2019)
The ventromedial prefrontal cortex (vmPFC) is known to play a key role in reward processing and decision making. However, its relative contribution to affect-rich ("hot") and affect-poor ("cold") decisions is not fully understood. Damage to vmPFC is associated with impaired performance on laboratory tasks of decision making under ambiguity and risk. In the current study, we tested the hypothesis that vmPFC is critical for adaptive risk taking under "hot" conditions specifically. Participants included patients with focal lesions in vmPFC, patient controls with damage in regions not including vmPFC, and healthy controls. They completed hot and cold versions of a dynamic risk-taking task, the Columbia Card Task (CCT). Relative to healthy controls and patient controls, vmPFC patients showed a strong overall increase in risk taking in the hot version of the CCT, despite preserved sensitivity to trial-level variation in risk. In the cold version, overall risk taking was similar among all three groups, even though vmPFC patients showed reduced sensitivity to trial-level variation in risk. Sensitivity to gain and loss magnitudes did not differ significantly among the groups, in either the hot or the cold CCT. These findings lend novel support to the hypothesis that the vmPFC is critical for adaptive decision making under affect-rich conditions.